STRATEGIC MANAGEMENT OF THE DEVELOPMENT OF A BORDER TERRITORIAL COMMUNITY IN THE REGIONAL-ADMINISTRATIVE MANAGEMENT SYSTEM - Dubnevych, Yuriy; Mahiiovych, Ihor (Social Development: Economic and Legal Issues, 2026)
The article examines the theoretical, methodological and applied foundations of strategic management of territorial community development in contemporary Ukrainian conditions, where local self-government simultaneously operates under decentralization reform, borderland interaction, demographic instability, infrastructure pressure and wartime uncertainty. The Rava-Ruska territorial community is selected as an analytical case because it combines several development advantages and vulnerabilities at the same time. On the one hand, it has a favorable location near the state border, access to an international transport corridor, agricultural and forestry potential, opportunities for logistics, cross-border cooperation and tourism. On the other hand, it faces labor migration, demographic decline, unequal access to services, infrastructure gaps and insufficient investment dynamics. The relevance of the study stems from the fact that strategic management at the community level can no longer be limited to the drafting of a one-time strategy document. It must become a permanent management system that connects the priorities of national regional policy, local resources, budgetary instruments, partnerships with residents, business and donors, as well as digital control of results. The legal framework, the updated state regional development policy and new transparency requirements for local self-government create the institutional basis for such a transition. However, actual effectiveness depends on the community’s ability to link strategic priorities with concrete projects, funding sources, measurable indicators and continuous feedback mechanisms. The purpose of the article is to substantiate a model for improving strategic management of the Rava-Ruska territorial community through the integration of strategic planning, SWOT-analysis, KPI-based monitoring, digital instruments and participatory governance. To achieve this purpose, the article applies a systemic, institutional, structural-functional, comparative, analytical and statistical approach. The empirical basis includes official community documents, the official community profile attached to the strategy, the 2024 strategy monitoring report, the official website of the city council, current legal acts, recent scholarly publications and the analytical manuscript provided by the author. The study demonstrates that the most productive model for the community is a strategic management system combining five interrelated blocks: a deep diagnosis of internal and external conditions; project and budget support for strategic priorities; digital monitoring of outcomes; institutionalized participation of residents and stakeholders; and alignment of local goals with national, regional and European development frameworks. It is proved that for a border community the most important components are logistics and spatial integration, development of an investment portfolio, support for local entrepreneurship, infrastructure modernization, expansion of coverage by basic municipal services and the creation of an open KPI system based on annual public reporting. The practical significance of the article lies in the possibility of using the proposed approaches by local self-government bodies for the updating of strategic documents, elaboration of new implementation plans, strengthening the link between strategy and budget, creating a public digital dashboard, broadening e-democracy tools and increasing institutional capacity under wartime conditions and during post-war recovery. The proposed model can also be adopted by other border communities facing a similar combination of resource advantages and governance risks.